The "God of Israel" in Judah's Bible Problems and Prospects - Stahl, Michael J. (2020)
The formulaic divine title "God of Israel" ([inline-graphic 01]) appears just over two hundred times in the Hebrew Bible. Yet, despite the epithet's prevalence in biblical writing and scholarly discourse, critical scholarship has left the Bible's use of the title largely unexamined. This article represents a first effort toward redressing this important scholarly desideratum, critically evaluating the Hebrew Bible's use of the title as a necessary prolegomenon to a history of the title's political and religious significance in ancient Israel and Judah.